Using Government Open Government Data Enriched With Provenance To Investigate Urban Mobility - Cruz, Sergio Manuel Serra da; Sampaio, Jonice de Oliveira (iSys - Journal of Information Systems, 2018)
One of the main challenges of smart cities applications in emerging countries is the limited availability of tools that increase the interaction and collaboration between government and civil society. This paper discusses the advantages of enriching open government data about public transport with data provenance. We present a distributed architecture and its prototype named BusInRio. We also, present use cases and experiments based on real users using open data enriched with provenance. Our experiments indicate the degrees of acceptance and correction of the proposal.